Pelatihan Branding Guna Meningkatkan Eksistensi Umkm Kelurahan Tanggung - Shinta Mutiara Putri; Mu’tasim Billah; Nurkholish Madjid; Muhammad Ryan Maulana; Adeev Jecona Diwanto (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Bank Sampah Matahari, KWT Sri Rejeki, and Peanut micro industry Mrs. Ida are micro industrys located in the Tanggung Village, Kepanjenkidul District, Blitar City. They have the same problem with other micro industrys, namely their lack of understanding of digitalization and the importance of identity for a business so that consumers can recognize their business, this causes their marketing to be limited on direct orders. Therefore, we created a branding socialization and training program for these micro industrys as a form of fulfilling our duty to serve the community. Branding is expected to be able to overcome the problems faced by micro industrys, especially in terms of digitalization. This community service implementation method is carried out through socialization and branding training, namely making logos, packaging labels using the Canva application. The evaluation was carried out by conducting interviews with the Bank Sampah Matahari, KWT Sri Rejeki, and micro industry Peanut Mrs. Ida to determine the level of participants' understanding of branding and the use of the Canva application. With this program, the micro industrys of Tanggung Village can have a business identity and packaging label to attract consumers to buy their products. The sustainability of this activity requires ongoing collaboration between the Head of Social Departement Tanggung Village, local community groups and the micro industry who take part in the training to introduce and love local products from the micro industry of Kelurahan Tanggung.